Evaluation of the Antibiotic Resistance Pattern at the Medical Services Administration Hospital in Khartoum, Sudan, 2021 - Abdellatif, Ashraf O.; Ali, Inas N.; Mohamed, Maha A.; Ibrahim, Maisoon A.; Mohamed, Wlaa A. (Journal for Research in Applied Sciences and Biotechnology, 2022)
The number of antibiotics available is limited and does not cover the growing antibiotic resistance challenge. Misuse and overuse of antibiotics act as factors that help in improving and increasing the problem of resistance to those currently being prescribed by doctors. The study was carried out at the Medical Services Administration Hospital (MSAH) in Khartoum, Sudan to investigate the antibiotic resistance pattern for the period between Dec. 2020 and Jan. 2022. The results showed that, in a total of different clinical samples that were collected and processed, a total number of 980 organisms were isolated. The result indicated that 345 out of the total isolates (35.20%) were Klebsiella pneumonia, 326 (33.27%) Escherichia coli, 154 (15.71%) Pseudomonas aeruginosa, 130 (13.27%) Proteus mirabilis, and 25 (2.55%) Staphylococcus aureus. The results showed that K. pneumonia was quite resistant to piperacillin, cefuroxime, and azithromycin. The amikacin, imipenem, and meropenem antibiotics showed significant activity against K. pneumonia. The isolates of E. coli showed significant resistance to azithromycin and were more sensitive to imipenem and meropenem. P. aeruginosa was resistant to penicillin, amoxicillin/clavulanic acid, and azithromycin in a big way, but it was very sensitive to cefuroxime, the drug used to treat strep throat infections. P. mirabilis was found to be resistant to nalidixic acid, nitrofurantoin, amoxicillin/clavulanic acid, and azithromycin. It showed good sensitivity to amikacin, imipenem, and meropenem. It was clear that S. aureus was resistant to cefuroxime, ceftriaxone, nitrofurantoin, and norfloxacin, while tests showed that it was sensitive to imipenem.